1998
DOI: 10.1038/bjc.1998.373
|View full text |Cite
|
Sign up to set email alerts
|

Association of tumour necrosis factor alpha and its receptors with thymidine phosphorylase expression in invasive breast carcinoma

Abstract: Summary Angiogenesis is an essential requirement for tumour growth and metastasis and is regulated by a complex network of factors produced by both stromal cells and neoplastic cells within solid tumours. The cytokine tumour necrosis factor alpha (TNF-ca) and the enzyme thymidine phosphorylase (TP) are two factors known to promote tumour angiogenesis. We have demonstrated recently that high numbers of tumour-associated macrophages (TAMs) are significantly associated with increased tumour angiogenesis and poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
119
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(125 citation statements)
references
References 20 publications
(24 reference statements)
3
119
0
3
Order By: Relevance
“…We have recently demonstrated an association between focal TAM infiltration and reduced relapse-free and overall survival in breast carcinomas. We have also shown that high levels of macrophages in focal areas (MØI) are associated with increased vascular density and that macrophage clusters are found in avascular areas of breast tumours (Leek et al, 1997). As macrophages have been shown to release such proangiogenic cytokines as vascular endothelial growth factor (Harney et al, 1998) tumour recrosis factor α (TNF-α) in response to hypoxia (Scannell et al, 1993), it is possible that, once macrophages reach hypoxic/ischaemic tumour sites, they may promote tumour growth and metastasis by releasing these factors to stimulate angiogenesis.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…We have recently demonstrated an association between focal TAM infiltration and reduced relapse-free and overall survival in breast carcinomas. We have also shown that high levels of macrophages in focal areas (MØI) are associated with increased vascular density and that macrophage clusters are found in avascular areas of breast tumours (Leek et al, 1997). As macrophages have been shown to release such proangiogenic cytokines as vascular endothelial growth factor (Harney et al, 1998) tumour recrosis factor α (TNF-α) in response to hypoxia (Scannell et al, 1993), it is possible that, once macrophages reach hypoxic/ischaemic tumour sites, they may promote tumour growth and metastasis by releasing these factors to stimulate angiogenesis.…”
mentioning
confidence: 66%
“…As macrophages have been shown to release such proangiogenic cytokines as vascular endothelial growth factor (Harney et al, 1998) tumour recrosis factor α (TNF-α) in response to hypoxia (Scannell et al, 1993), it is possible that, once macrophages reach hypoxic/ischaemic tumour sites, they may promote tumour growth and metastasis by releasing these factors to stimulate angiogenesis. Therefore, the purpose of this study was to assess quantitatively the degree of central necrosis in a consecutive series of invasive breast carcinomas and to examine its relationship to both focal microphage infiltration and angiogenesis, as measured by quantitative CD68 and CD31 immunohistochemistry of vessel and macrophage 'hotspots' respectively (Fox et al, 1995;Leek et al, 1996Leek et al, , 1997.…”
mentioning
confidence: 99%
“…Many cytokines and chemokines are alertable by hypoxia and oxidative stress, which is a most important physiological difference between tumor and normal tissue (Balkwill and Mantovani, 2001) .TNF is a major mediator of inflammation and can be detected in malignant or stromal cells in human cancers especially in breast, ovarian, prostate, bladder and colorectal cancer (Naylor et al, 1993;Burke et al, 1996). In breast cancer infiltrating leucocytes are a major source of TNF (Leek et al, 1998). On the other hand lymphocytic response is the main component in the control of cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…In a number of immunohistochemical studies TNF-α has appeared in particular in the cytoplasm of inflammatory cells and tumour-associated macrophages (Pusztai et al, 1994), although a proportion of neoplastic cells have shown to be TNF-α positive in some human cancers such as breast (Leek et al, 1998) and lung carcinomas (Tran et al, 1998). Substantially different results have been obtained in these human models: in breast carcinoma a significant association has been found between TNF-α and thymidine phosphorylase expression, which is a factor known to promote tumour angiogenesis (Fajardo et al, 1992;Fox et al, 1996); in lung cancer, where neoangiogenesis seems to play an unfavourable prognostic role, TNF-α expression has shown to produce a better clinical outcome (Tran et al, 1998).…”
Section: Tnf-α Expressionmentioning
confidence: 99%